واقع العمل المساحي عند تنفيذ الأبنية في سورية - يحيى منير (Latakia University Journal -Engineering Sciences Series, 2016)
The research aims to study the reality of areal work in Syria by the public and private sectors, starting with the study phase through the implementation phase and ending with investment. In this research, statistical and analytical studies of a sample of local projects have been conducted by using (SPSS) software where the samples were divided into four case studies showing areal work and where any deviation from the desired objectives could happen. this research suggests, within its primary objective model, a filing system for areal work for buildings that could be used as a reference for all topographical office work in the public and private sector. يهدف البحث إلى دراسة واقع العمل المساحي عند تنفيذ الأبنية في سورية من قبل القطاعين العام والخاص بدءا من مرحلة الدراسة مرورا بمرحلة التنفيذ وانتهاء بالإستثمار لها. تم في البحث إجراء دراسة إحصائية وتحليلية لعينة من المشاريع المحلية باستخدام برنامج ( SPSS ) وذلك بتقسيم العينة إلى أربع حالات دراسية تبين واقع العمل المساحي فيها وانحرافها عن الأهداف المرجوة. يقترح البحث ضمن هدفه الأساسي نموذجا لإضبارة العمل المساحي الخاصة بالأبنية لتكون مرجعا لجميع أعمال المكاتب الطبوغرافية في القطاعين العام والخاص.